Answer:
a) (x + 6)(x - 4)
Explanation:
a) (x+1)^2 - 25
=(x+1)(x+1) - 5 x 5
Remember the formula for a difference of two squares is
a^2 – b^2 = (a + b)(a – b) or (a – b)(a + b)
so a = x+1 and b = 5
therefore to factorise it would be
(x + 1 + 5)(x + 1 - 5)
= (x + 6)(x - 4)
b) For the next one, it's a similar:
root 49 is 7, and the equation (1 - x) has been squared so
a = 7 and b = - (1 - x)
The last part is the same as a), if you still need help, just ask me :)
Tip: don't forget to incorporate the negative, it's important!
Hope this helped,
Cate